Androgenetic alopecia - just a cosmetic defect or a biomarker and risk factor for systemic diseases? - literature review - Dawid Suwała; Natalia Pokrywka; Marcelina Polak; Klaudia Koryszko; Paulina Hetnar; Magdalena Tomala; Sebastian Kiper; Milena Fortuna; Sławomir Toczek; Katarzyna Jastrowicz-Chęć (Journal of Education, Health and Sport, 2025)
Introduction: Androgenetic alopecia (AGA) is the most common cause of hair loss. It has traditionally been considered a cosmetic defect, but a growing body of evidence suggests that it may serve as a biomarker and risk factor for systemic diseases, suggesting its potential role in early disease detection and prevention.